Hitchhiker's Guide to Inflation in Libya - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2013)
This paper presents an empirical investigation of inflation dynamics in Libya over the period 1964-2010, using cointegration and error correction models. While inflation inertia is found to be a key determinant of consumer price inflation, the econometric results indicate that government spending, money supply growth, global inflation, and exchange rate pass-through play central roles in the inflation process. These findings are broadly consistent with the experience of other countries that are natural resource dependent. We also find evidence that the imposition and subsequent removal of international sanctions on Libya had a noteworthy impact on consumer price inflation. Collectively, our estimates indicate that the deviations from an equilibrium path initiate significant adjustments in inflation dynamics, and that closer coordination between monetary and fiscal policies would improve the balance between economic growth and price stability.